Chelating ligands as electrolyte solvent for rechargeable zinc-ion batteries - Verma, Vivek (2021)
Rechargeable zinc-ion batteries (RZIBs) are mostly powered by aqueous electrolytes. However, uncontrolled water interactions often confer a small voltage window and poor battery capacity retention. Here, we explore replacing water with ethylene glycol as the primary solvent in zinc electrolyte formulations. The assembled batteries reveal suppressed electrolyte-induced parasitic reactions, leading to (1) expanded voltage stability windows up to 2.2 V, (2) prolonged zinc stripping/plating stability up to 2.4 times longer compared to the water-based counterparts, and (3) doubled cathode capacity retentions as observed in full-cell Zn-FeVO4 RZIBs. Using a combination of synchrotron EXAFS and FTIR, we investigate the molecular level salt-solvent interactions and explain how the chelation ability of EG ligands reduces parasitic reactions to enable the enhanced electrochemical performances. The structural insights should provide guidelines on the selection of salt, concentration, and chelating solvents for robust multivalent-ion battery systems.